2006
DOI: 10.1159/000090594
|View full text |Cite
|
Sign up to set email alerts
|

Aggressiveness, Anger and Eating Disorders: A Review

Abstract: Anger and aggressive behaviours, especially those self-directed, are frequent in subjects suffering from anorexia nervosa and bulimia nervosa. They increase the complexity of the clinical features, change the prognosis and cause a more difficult management of these disorders. In order to elucidate the complex relationships between eating disorders, anger and aggressiveness, the history of traumatic experiences, the prevalence of dissociative, obsessive, impulsive and compulsive symptoms, as well as the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
61
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 222 publications
8
61
0
Order By: Relevance
“…Research findings indicate that anger is a significant underlying emotion contributing to disordered eating (Engel et al, 2007;Fox & Power, 2009;Harrison, Sullivan, Tchanturia, & Treasure, 2010;Ioannou & Fox, 2009;Quinton & Wagner, 2005). Patients with bulimia often feel anger and may impulsively direct it toward others or toward objects (Truglia et al, 2006). Patients suffering from anorexia nervosa can feel anger as a terrifying emotion that needs to be avoided (by concentration on food, body and weight), needs to be suppressed, for example by physical activity, and released by anorectic self-control or self-harm (Espeset, Gulliksen, Nordbø, Skårderud, & Holte, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Research findings indicate that anger is a significant underlying emotion contributing to disordered eating (Engel et al, 2007;Fox & Power, 2009;Harrison, Sullivan, Tchanturia, & Treasure, 2010;Ioannou & Fox, 2009;Quinton & Wagner, 2005). Patients with bulimia often feel anger and may impulsively direct it toward others or toward objects (Truglia et al, 2006). Patients suffering from anorexia nervosa can feel anger as a terrifying emotion that needs to be avoided (by concentration on food, body and weight), needs to be suppressed, for example by physical activity, and released by anorectic self-control or self-harm (Espeset, Gulliksen, Nordbø, Skårderud, & Holte, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that treatment of non-suicidal self-injury in ED should focus on stabilizing affective states rather than on reducing affects like anger (Vansteelandt et al, 2013). Despite such findings, there is a lack of research on how to approach anger and aggression in the treatment of ED (Fassino, Daga, Piero, & Rovera, 2002;Krug et al, 2008;Miotto et al, 2003;Truglia et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations